2016
DOI: 10.1530/jme-15-0268
|View full text |Cite
|
Sign up to set email alerts
|

60 YEARS OF POMC: The proopiomelanocortin gene: discovery, deletion and disease

Abstract: The cloning of the bovine proopiomelanocortin (POMC) cDNA in 1978 by Nakanishi and colleagues was the result of a remarkable series of exacting and ingenious experiments. With this work, they instantly confirmed the single precursor hypothesis for adrenocorticotrophic hormone-β-lipotropin, as it was then known, and in so doing revealed the existence of additional, largely unpredicted, N-terminal peptides that together formed the POMC precursor peptide. This work paved the way for a host of additional studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 70 publications
0
18
0
1
Order By: Relevance
“…The same year, cloning cDNA from pituitary pars intermedia provided the gene sequence for bovine POMC (265) which was independently confirmed by protein sequencing (264). Similar approaches identified the sequences for the human (72,391), mouse (407), rat (105), and pig (38) genes (69). Despite the sequence being highly conserved, there is some variation in the lengths of some of the peptides in different species (FIGURE 2).…”
Section: The Emergence Of the Full Structure Of Pomcmentioning
confidence: 80%
See 1 more Smart Citation
“…The same year, cloning cDNA from pituitary pars intermedia provided the gene sequence for bovine POMC (265) which was independently confirmed by protein sequencing (264). Similar approaches identified the sequences for the human (72,391), mouse (407), rat (105), and pig (38) genes (69). Despite the sequence being highly conserved, there is some variation in the lengths of some of the peptides in different species (FIGURE 2).…”
Section: The Emergence Of the Full Structure Of Pomcmentioning
confidence: 80%
“…Many of these studies were carried out using techniques such as Northern blot and PCR and show expression, but not whether translation to the protein or processing occurs in these locations. In fact, it has been shown that many of these tissues contain a shorter mRNA transcript that would not be translated and therefore no peptide produced (69). Furthermore, in both humans and murine mod-recombination in regions including the hippocampus, regions of the cortex, and midbrain (284).…”
Section: Tissue Localization Of Pomcmentioning
confidence: 99%
“…We (Kilianova et al 2006, Roy et al 2007 and others have been able to decipher the mechanisms of expression and regulation of MC2R in melanocortin-2 receptor accessory proteins (MRAPs) expressing cells. The role of MRAP1 as well as the relative roles that the various forms of MRAPs identified thereafter has been documented in several recent reviews (Hinkle & Sebag 2009, Cooray & Clark 2011, Jackson et al 2015, Clark 2016. Another particularity is that ACTH treatment of adrenocortical cells (4 h or more) increases the expression of MC2R (Penhoat et al 1989, Mountjoy et al 1994), as well as the level of MRAP and MRAP2 (Hofland et al 2012).…”
Section: Overview Of the Acth-mc2r Complexmentioning
confidence: 93%
“…Confirmation of the single-precursor concept was provided by the cloning of the POMC gene by Nakanishi and coworkers; work reviewed by Adrian Clark (Clark 2016). Cloning of POMC additionally revealed undiscovered N-terminal components of this precursor whose potential biological function is reviewed by Andrew Bicknell (Bicknell 2016).…”
mentioning
confidence: 98%